Evaluation of fermentation potential of wild and UV-mutated yeasts screened from traditional murcha - Subba, Jeny; Rai, Basanta Kumar; Limbu, Dil Kumar; Rai, Sangen Ruma (Himalayan Journal of Science and Technology, 2018)
Murcha (an amylolytic starter) from different parts of Eastern Nepal were screened for fermentative yeasts. The most potential one was UV-mutated (8W lamp at λ = 254 nm and an intensity of 44.21 Wm-2 for 5-50 s) to study the effect of mutation on growth and fermentation properties. Respiratory-deficient mutants (RDMs) that resulted from the mutation were identified by triphenyl tetrazolium chloride (TTC) overlay technique and replica-plated for further isolation. Cell growth, substrate utilization, and ethanol yield of the mutants were compared with normal cells by carrying out fermentation in high-test cane molasses broth of 30 °Bx. An exhaustive screening of the samples resulted in only two murcha viz., from Laxmimarga (LM) and Udayapur (UD), having the desirable fermentation properties. UV-mutation study of UD and LM yeasts (both identified as strains of Saccharomyces cerevisiae) showed 8-12% survival and 22% RDMs yield of the survived cells. Out of the 8 randomly selected RDMs, only UDm4 (colony No. 4 from UD) showed fermentation properties worth further investigation. Comparison of UD, LM and UDm4 by fermenting molasses (high test) broth of 30°Bx showed the least growth of UDm4 but the highest alcohol yield (9% and 16% more compared to UD and LM, respectively). The present finding indicates that it is possible to improve fermentation properties of feral yeasts from murcha by relatively simple UV-mutation approach. Finding the right mutant (the selective screening part), however, may involve considerable time and effort.